2018
DOI: 10.1007/s11605-018-3712-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy Based on Indocyanine Green Test for Chemotherapy-Associated Liver Injury and Long-Term Outcome in Colorectal Liver Metastases

Abstract: The presence of an impaired ICG test result or PLI did not affect the long-term outcome after individually selected operative procedure. However, patients undergoing MHML had a higher possibility of developing a > 25% splenic volume increase after hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Studies showed that receipt of 12 or more weeks of neoadjuvant chemotherapy was associated with the increased hepatotoxicity in the form of steatohepatitis or hepatic sinusoidal obstruction, depending on the chemotherapy regimen. Therefore, hepatic resections in patients with longer chemotherapy duration are potentially prohibitive or at the very least require a larger FLR (30%‐40%) to avoid post‐hepatectomy liver failure . To improve the size of the FLR, techniques such as portal vein embolization (PVE) and portal vein ligation (PVL) were brought into clinical practice; such techniques induce atrophy of the liver segments to be resected and hypertrophy of the contralateral FLR.…”
Section: Surgical Therapymentioning
confidence: 99%
“…Studies showed that receipt of 12 or more weeks of neoadjuvant chemotherapy was associated with the increased hepatotoxicity in the form of steatohepatitis or hepatic sinusoidal obstruction, depending on the chemotherapy regimen. Therefore, hepatic resections in patients with longer chemotherapy duration are potentially prohibitive or at the very least require a larger FLR (30%‐40%) to avoid post‐hepatectomy liver failure . To improve the size of the FLR, techniques such as portal vein embolization (PVE) and portal vein ligation (PVL) were brought into clinical practice; such techniques induce atrophy of the liver segments to be resected and hypertrophy of the contralateral FLR.…”
Section: Surgical Therapymentioning
confidence: 99%
“…In the present study, some patients did not achieve enough volume increase within 14 days after PVE: that is, we generally regarded FLR volume after PVE as insufficient, when FLR increased by less than 10% and did not reach approximately 50% of TLV, because successful PVE could reportedly achieve approximately 10% increase of FLR 24,25 and resection with FLR < 50% (e.g., right hepatectomy) was not recommended for those with impaired liver function in Makuuchi's criteria. 16,17 In these cases, we waited for a sufficient FLR | 1747 increase for weeks, or given that some embolized portal branches recanalized, additional PTPE for the branches using absolute ethanol was performed to reduce the risk of liver failure after major hepatectomy. Consequently, because US and CT scan showed significantly slower liver volume increase after PVE in patients with impaired liver function (i.e., Group B and C), such patients required a longer interval from PVE to successive hepatectomy compared to those with normal liver function (i.e., Group A).…”
Section: Discussionmentioning
confidence: 99%
“…We planned PVE when a patient required (extended) right hepatectomy for radical resection (e.g., when the tumors involved major vessels; or when most of the tumors were located in a hemi-liver) and an FRL volume for the liver functional reserve after successive hepatectomy was expected to be sufficient, based on our longestablished criteria for liver resection (Makuuchi's criteria). 16,17 If ICG-R15 was less than 10% and the ratio of FLR was less than 40%, preoperative PVE was indicated. If ICG-R15 was greater than 10% and the ratio of FLR was less than 60%, preoperative PVE was also indicated.…”
Section: Patients Selectionmentioning
confidence: 99%
“…Several studies have reported on the impact of FLR volumetric analysis on the outcomes of LR[ 30 , 31 ]. Generally speaking, the FLR size should be at least 20% for patients with normal livers and those who have received chemotherapy for no more than 12 wk[ 32 ]; however, considering that there is significant chemotherapy-associated steatohepatitis or sinusoidal obstruction in those receiving preoperative chemotherapy for more than a 12-wk duration or more than eight cycles, this cut-off value should be increased to 30%–40% in order to avoid postoperative liver failure[ 32 , 33 ]. The reason for this increase is that the risks of major complications, liver failure, and mortality increase to 47%, 20%, and 13%, respectively, if the FLR is < 20% of the total volume[ 34 ].…”
Section: Evaluation Of Resectability Of Lmmentioning
confidence: 99%
“…A study by Wakiya et al[ 38 ] has found that the preoperative ICG retention rate at 15 min (ICGR15) did not strongly correlate with the pathological sinusoidal injury and steatohepatitis scores in CRLM patients. The sensitivity and specificity of the ICG test for detecting pathological liver injury were 47% and 75%, respectively[ 33 ]. In order to perform a safe radical LR, it is necessary to estimate the hepatic functional reserve of the chemotherapy-associated liver based on a combination of several clinical indicators and not only rely on the ICG test.…”
Section: Evaluation Of Resectability Of Lmmentioning
confidence: 99%